Comparative impact of insect growth regulators on mortality and development of Amrasca biguttula (Hemiptera: Cicadellidae) - Sabrine Attia; Shimat V. Joseph (PLoS ONE, 2026)
The two-spot cotton leafhopper, Amrasca biguttula (Ishida) (Hemiptera: Cicadellidae), recently detected in the United States, represents an emerging threat to cotton, vegetable, and ornamental crops. Insect growth regulators (IGRs) are considered reduced-risk insecticides. Despite their availability to growers and effectiveness on several piercing and sucking insects, the lethal effects of IGRs on the development of A. biguttula remain poorly understood. Thus, the objective of this study was to determine the effects of common IGRs on various stages of A. biguttula . We evaluated four IGRs: pyriproxyfen, novaluron, azadirachtin, and buprofezin applied at field-recommended rates, alone or combined with nonionic and organosilicone adjuvants, on survival, molting disruption (exuviae production), and longevity of early (1 st -2 nd ), intermediate (3 rd -4 th ), and late (5 th ) nymphal instars, as well as adults using leaf dip and adaxial leaf smear bioassays. All IGRs induced significant, stage-dependent lethal effects. Mortality of 1 st –2 nd instars reached over 90% with buprofezin and novaluron, and molting inhibition reached up to 55%, indicating strong effects of the tested insecticides. The chitin biosynthesis inhibitors buprofezin and novaluron caused rapid mortality, strong molting inhibition, and reduced longevity, particularly in early and intermediate instars. Pyriproxyfen and azadirachtin elicited weaker, delayed responses, with limited effects on late instars and adults. Although adding adjuvants slightly enhanced efficacy, their overall impact was marginal. These findings demonstrate that IGRs can profoundly disrupt A. biguttula population development through interference with insect growth and metamorphosis, supporting their use as selective and sustainable tools in integrated pest management programs targeting this invasive leafhopper.